Antibiotic Susceptibility of Bacterial Strains Isolated from Urinary Tract Infections in a Private Laboratory of Dhaka City - Uddin, Bhuiyan Mohammad Mahtab; Roy, Sushmita; Hossen, M Mokter; Akhand, Faria; Bari, Sumia; Chowdhury, Sarowar Jahan; Mahjabin, Mosfika; Salman, Mohammad Nahid (Bangladesh Journal of Medical Microbiology, 2023)
Background: Urinary tract infection (UTI) is one of the most common infections worldwide. Objective: The aim of the study was to identify different species of microorganisms, along with their antimicrobial susceptibility pattern, causing urinary tract infection in outpatient and indoor patients at Farazy Hospital Ltd, Dhaka, Bangladesh. Methodology: This retrospective study was conducted using urine culture and sensitivity reports collected retrospectively from records maintained in the Department of Microbiology over a one-year period from January 2020 to December 2020 in a tertiary care hospital. Results: UTI was more common in females (68.39%) than in males (31.61%). Among the uropathogens isolated Escherichia coli (67.6%) was found to be the predominant organism followed by Staphylococcus aureus (12.49%), Klebsiella species (8.23%), and Staphylococcus saprophyticus (6.83%) of total cases. The most common isolates were E. coli showed high sensitivity to tigecycline (97.32%), followed by meropenem (95.88%) and imipenem (95.68%). It was found to be highly resistant to ceftriaxone (62.89%) and ceftazidime (54.12%). Conclusion: In conclusion, Escherichia coli species is the most common organism causing UTI with high resistance to the commonly prescribed antimicrobial drugs. Bangladesh Journal of Medical Microbiology, January 2022;16(1):3-7